Failure of compression molded all-polyolefin composites studied by acoustic emission - I. Z. Halasz; G. Romhany; A. Kmetty; T. Barany; T. Czigany (eXPRESS Polymer Letters)
This paper is aimed at studying the failure behavior of polyolefin-based self-reinforced polymer composites (SRPCs) via acoustic emission (AE). Three matrix materials (ethylene octene copolymer (EOC), polypropylene-based thermoplastic elastomer (ePP), random polypropylene copolymer (rPP), and three kinds of reinforcing structures of PP homopolymer (unidirectional (UD), cross-ply (CP) and woven fabric (WF)) were used. SRPCs were produced by compression molding using the film-stacking method. The composites were characterized by mechanical tests combined with in situ assessment of the burst-type AE events. The results showed that rPP matrix and UD reinforcement produced the greatest reinforcement, with a tensile strength more than six times as high as that of the matrix and a Young’s modulus nearly doubled compared to the neat matrix. The number of the detected AE events increased with increasing Young’s modulus of the applied matrices being associated with reduced sound damping. The AE amplitude distributions shows that failure of the SRPC structure produces AE signals in a broad amplitude range, but the highest detected amplitude range can be clearly linked to fiber fractures.